PENGARUH OPINI AUDIT DAN REPUTASI AUDITOR TERHADAP VOLUNTARY AUDITOR SWITCHING (STUDI PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Wawo, Andi Basru; Nurdin, Emillia; Yusran, Selfy Dewita (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACTÂ Â Â Â Â Â Â Â Â  This study aims to exam The Influence of Audit Opinion and Auditor Reputation toward to Voluntary Auditor Switching. The population in this study is the Real Estate and Property companies listed at the Indonesia Stock Exchange in 2010 until 2014. There are 39 samples achievemented using purposive sampling method. Analysis The Influence between independent and dependent variables used the multiple linear regression analysis and SPSS version 21.Â Â Â Â Â Â  This study indicated determination coeffiecient result for the Audit Opinion and Auditor Reputation toward to Voluntary Auditor Switching Â = 0.113. Thatâs number have meaning contribution Audit Opini and Auditor Reputation toward to Voluntary Auditor Switching is 11,3% whereas remain Â 86,7% Â achievement from other factorsâ contribution.Â Â Â Â Â  The result this study indicated that simultaneous according audit opinion and auditor reputation significantly influence toward to voluntary auditor switching. According partial, audit opinion influenced negative significantly toward to voluntary auditor switching. Auditor reputation variable influenced negative significantly toward to voluntary auditor switching.Â Keywords: Audit Opinion, Auditor Reputatiton, Voluntary Auditor Switching.Â